Détection automatique des parcelles sur les plans napoléoniens : comparaison de deux méthodes - Jean-Michel Follin; Élisabeth Simonetto; Anthony Chalais (Humanités Numériques)
The most detailed geographic description of France’s whole 19th-century territory is the Napoleonic cadastre. It contains a wealth of information (e.g. cadastre lot structure, lot numbering, rivers and road shapes, toponymy, buildings…) which underpin most historical studies of land usage and transformation. We therefore decided to develop a semi-automatic toolchain able to vectorise, georeference and combine scanned old cadastre sheets in order to build a multi-epoch database describing land property. In this article, we focus on the automatic vectorisation of the parcels’ shapes and assess the respective merits of two methods we tested: the first based on the Probabilistic Hough Transform (PHT) and the second on the Line Segment Detector (LSD) algorithm. After explaining how we implemented these two methods, we present the results, which show that the LSD approach performs better on the oldest cadastre sheets.